Mechanical Characterization of Cemented Paste Backfill - Andrew Pan; Murray Grabinsky (Eng, 2023)
Mechanical characterization is important to the design and analysis of cemented paste backfill (CPB) structures. Unconfined compressive strength (UCS) tests have been widely used owing to their relative simplicity to characterize a material’s response to unconfined compressive loading. However, the UCS represents a single strength parameter and does not fully describe the material’s strength (or failure) envelope. In this study, we analyzed UCS tests with direct shear and uniaxial tensile strength tests conducted on the same CPB materials to provide mechanical characterization of CPB under a more complete range of loading conditions. The results demonstrate the Mohr–Coulomb failure envelope provides a consistent description of strengths arising from the three different test methods. Furthermore, a better estimate of the tensile strength is UCS/4, which is considerably higher than the conventional assumption that the tensile strength is equal to USC/10 or UCS/12. This has a significant impact on the assessed required strengths particularly for undercut designs using Mitchell’s sill mat analysis method and suggests that in future the conventional UCS tests should be complemented with direct tension and direct shear tests to improve underground designs using CPB.